Analisis Kondisi Polusi Udara Berdasarkan Perubahan Waktu Menggunakan IoT dan Logika Fuzzy: Solusi Mencegah Dampak Polusi Terhadap Kesehatan - Muhammad Yudha; Susilawati Susilawati (INCODING: Journal of Informatics and Computer Science Engineering, 2025)
Identifying air pollution is a serious problem in various cities including Medan city. In this article, the use of IoT sensor-based mamdani fuzzy inference rules to identify air pollution in Medan city is discussed. Data collection is done through devices and systems built using IoT sensor devices. The IoT devices are installed in three different locations namely on Sei Deli, Tembung and KIM roads to monitor and collect air pollution data in real-time. Fuzzy inference rules are then used to process the sensor data and identify air pollution based on predefined threshold values. In addition to pollution factors, the determination of the time scale, namely early morning, morning, afternoon, evening and night is also a variable to identify air pollution based on time. The results show that the system built can identify air pollution based on data obtained through 3 devices with an average value of pollution in the "Medium" category.